EVALUASI KINERJA GURU BERSERTIFIKASI - Alexander Kismanto Utomo; Bambang Suteng Sulasmono; Mawardi Mawardi (Universitas Negeri Malang, 2019)
Abstract: This study aims to evaluate the performance of certified teachers Kalam Kudus Christian Elementary School in Surakarta assessed based on (1) planning and preparation of learning, (2) class management, (3) learning process, and (4) professional teacher responsibility. This research is an evaluative research using Charlotte Danielson Model, with simple qualitative and quantitative method. The research subjects were seven certified teachers at Kalam Kudus Christian Elementary School Surakarta. Data collection through interviews, observation, and document study. Moderate data collection instruments include teacher performance assessment rubric, interview guides, and questionnaires. The data validity test is done by source and technique triangulation. The results of this study: (1) the certified teacher performance in preparing and planning of learning is included in the excellent category, (2) the certified teacher performance in managing the classes included in the good category; (3) the certified teacher performance in the learning process included in the excellent category, and (4) the certified teacher performance in their professional responsibilities is included in the excellent category. Abstrak: Penelitian ini bertujuan untuk mengevaluasi kinerja guru bersertifikat di SD Kristen Kalam Kudus Surakarta dinilai berdasarkan (1) perencanaan dan persiapan pembelajaran, (2) pengelolaan kelas, (3) proses pembelajaran, dan (4) tanggung jawab profesional. Penelitian ini merupakan penelitian evaluatif dengan menggunakan Model Charlotte Danielson, dengan metode kualitatif dan kuantitatif sederhana. Subjek penelitian adalah tujuh guru bersertifikat di SD Kristen Kalam Kudus Surakarta Teknik pengumpulan data menggunakan wawancara, observasi, dan studi dokumen. Instrumen pengumpulan data menggunakan rubrik penilaian kinerja guru, panduan wawancara, dan kuesioner. Uji validitas data menggunakan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa (1) kinerja guru bersertifikat dalam mempersiapkan dan merencanakan pembelajaran termasuk dalam kategori sangat baik, (2) kinerja guru bersertifikat dalam mengelola kelas termasuk dalam kategori baik; (3) kinerja guru tersertifikasi dalam proses pembelajaran termasuk dalam kategori sangat baik, dan (4) kinerja guru tersertifikasi dalam tanggung jawab profesionalnya dikategorikan sangat baik.